The Brighton Collaboration standardized template for collection of key information for benefit-risk assessment of protein vaccines. Issue 35 (31st July 2020) - Kochhar, Sonali; Kim, Denny; Excler, Jean-Louis; Condit, Richard C.; Robertson, James S.; Drew, Stephen; Whelan, Mike; Wood, David; Fast, Patricia E.; Gurwith, Marc; Klug, Bettina; Khuri-Bulos, Najwa; et al.
Abstract: Several protein vaccine candidates are among the COVID-19 vaccines in development. The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) has prepared a standardized template to describe the key considerations for the benefit-risk assessment of protein vaccines. This will help key stakeholders to assess potential safety issues and understand the benefit-risk of such a vaccine platform. The structured and standardized assessment provided by the template would also help contribute to improved public acceptance and communication of licensed protein vaccines.